Increased Substance P Immunoreactivity in Ipsilateral Knee Cartilage of Rats Exposed to Lumbar Spine Injury. (April 2020) - Duarte, Felipe C. K.; Zwambag, Derek P.; Brown, Stephen H. M.; Clark, Andrea; Hurtig, Mark; Srbely, John Z.
Augmented expression of substance P (SP) in the cartilaginous tissue has been shown to promote degenerative changes in the cartilaginous matrix of distal contralateral articular joints via neurogenic inflammation post monoarthritis-induction contributing to the symmetrical spread of osteoarthritis (OA). However, no studies have explored whether similar changes are also present within neurosegmentally linked ipsilateral heterologous cartilage. Objective: The present study aimed to investigate whether experimentally induced lumbar facet-joint OA lead to degenerative changes and enhanced SP expression within the ipsilateral neurosegmentally linked tibiofemoral cartilage. Methods: Adult male Sprague-Dawley rats were assigned to left side L5-L6 facet mechanical compression injury (surgery) ( n = 6), L5-L6 facet exposure with no compression (sham) ( n = 5), or naïve (no surgery) ( n = 4) groups. The morphology of the tibiofemoral articular cartilage was assessed using a modified Mankin scoring system. Immunohistochemistry was used to examine the density of chondrocytes stained positive for SP (cells/cm 2 ) in the ipsilateral tibiofemoral cartilage at 28 days postintervention. Results: Tibiofemoral cartilage in the surgery group showed consistent loss of superficial zone chondrocytes, mild roughening of the articular surface and occasional chondrocyte clusters as well as a greater density of SP mainly in the superficial cartilage zone compared with sham and naïve groups, although they also had a basic SP-expression. Conclusion: Our results support the hypothesis that neurogenic mechanisms may mediate the spread of SP to neurosegmentally linked heterologous joints affecting the distal cartilage homeostasis. These findings contribute additional insight into the potential role of neurogenic inflammation with implications in the pathophysiology of chronic inflammatory joint disease and OA.